2020
DOI: 10.29219/fnr.v64.4267
|View full text |Cite
|
Sign up to set email alerts
|

Cyclocarya paliurus ethanol leaf extracts protect against diabetic cardiomyopathy in db/db mice via regulating PI3K/Akt/NF-κB signaling

Abstract: Background: Diabetic cardiomyopathy (DCM) is a serious complication of diabetes that can lead to significant mortality. Cyclocarya paliurus is a tree, the leaves of which are often utilized to prevent and treat diabetes mellitus. Whether C. paliurus leaves can prevent or treat DCM, however, it remains to be formally assessed. The present study was therefore designed to assess the ability of C. paliurus to protect against DCM in db/db mice. Methods: Male wild-type (WT) and db/db mice were administered C. paliur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
9
1
Order By: Relevance
“…These enzymes are activated by either upstream tyrosine kinase receptors or G protein-coupled receptors and mediate multiple cellular processes (62). PI3K/Akt signaling is essential for regulation of inflammatory responses, at least in part via controlling intracellular NF-κB activity (63). Our data did not show NF-κB associated with orange juice intake.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…These enzymes are activated by either upstream tyrosine kinase receptors or G protein-coupled receptors and mediate multiple cellular processes (62). PI3K/Akt signaling is essential for regulation of inflammatory responses, at least in part via controlling intracellular NF-κB activity (63). Our data did not show NF-κB associated with orange juice intake.…”
Section: Discussioncontrasting
confidence: 48%
“…Experimental studies on cancer, myocardial ischemia/reperfusion injury, and arthritis have already shown the effects of hesperidin in modulation of the PI3K-Akt pathway (62)(63)(64)(65). The PI3K/Akt signaling pathway regulates various cellular responses such as cell growth, proliferation, survival, metabolism, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Further mechanistic exploration revealed that C. paliurus extract reduced the expression of NF- κ B and myocarditis by activating the PI3K/Akt signaling pathway, improving antiapoptotic Bcl-2, and reducing prapoptotic cle-caspase-3, cle-caspase-9, and Bax, to reduce myocardial inflammation and injury in mouse models. Therefore, it is speculated that it may effectively reduce pathological damage and fibrosis of the heart tissue in diabetic patients [ 100 ].…”
Section: Application Of C Paliurus In the Complication Of T2dmmentioning
confidence: 99%
“…Its leaves (commonly known as "magical tea" and "sweet tea") have several biological activities such as antiinflammatory, antihyperlipidemic, antioxidant, antihypertensive, antihyperglycemic, and antiobesity effects (Kurihara et al, 2003;Wang et al, 2013;Xie & Xie, 2008;Yan, Jiang, & Xu, 2020). Male Given its various functions and lack of significant adverse effects, C. paliurus leaf extract may have therapeutic value in diabetic cardiomyopathy (Wang et al, 2020).…”
Section: Cyclocarya Paliurus Extractmentioning
confidence: 99%